SERVQUAL evaluation applied in a company in the metallurgical sector - Moura, Ricardo Ribeiro; Rocha, Ricardo Rodrigues; Moura, Bruno Furtado de (Brazilian Journal of Production Engineering, 2025)
The quality of service provided is related to customer perception, which is difficult to measure. The quality-of-service indicators are based on an instrument to measure the difference between expectation and perception of the customer served. The method used is the service, which evaluates the results related to the general and individual index of the perceived quality of the service. Using a Pareto diagram, it is possible to analyze the services that need improvements and investigate the causes using the Ishikawa diagram. Therefore, this research aimed to address the quality of services provided by a metallurgical company according to the perception of its customers. Of the five dimensions analyzed, one presented more excellent perception than expectation. However, it was realized that the level of demand and expectation of customers was also high. Of the six dissatisfaction problems raised in the questionnaire, 2 correspond to 77.5% of the total customer complaints: payment options and punctuality. At the end of the research, improvements relevant to the highlighted problems were recommended. As analyzed by the study, quality management is of fundamental importance in business management, allowing customer expectations, reducing problems, and raising employee appreciation.